Suppressed ion chromatography methods for the routine determination of ultra low level anions and cations in ice cores - Mark Curran; Palmer, AS (2001)
The concentration of trace ionic species in snow and ice samples was determined using suppressed ion chromatography (IC) with conductivity detection and ultra-clean sample preparation techniques. Trace anion species were determined in a single 24-min run by combining sample preconcentration with gradient elution using Na2B4O7 eluent. The detection limits (ranging from 0.001 to 0.006 Î¼M) are the lowest reported in the literature. Cation species were analysed by direct injection of 0.25 ml and isocratic elution with a H2SO4 eluent. The clean preparation techniques showed no evidence of a difference (Student's t-test) between Milli-Q water samples analysed directly and processed Milli-Q ice samples. These robust, ultra-clean IC methods were routinely applied to the analysis of large number of samples to produce a high-resolution trace ion ice core record from Law Dome, East Antarctica. Â© 2001 Elsevier Science B.V.